High-dispersion iron phosphate material and preparation method thereof, positive electrode material and lithium ion battery
By introducing ultrasonic treatment during the preparation of iron phosphate, the problems of poor conductivity of iron phosphate materials and slow lithium ion diffusion kinetics in the positive electrode materials of lithium-ion batteries are solved, and high dispersion and small particle size anhydrous iron phosphate is achieved, which improves the capacity and rate performance of the battery.
Patent Information
- Application Number
- CN202411741542.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-11-29
AI Technical Summary
The existing iron phosphate materials have poor conductivity and slow lithium ion diffusion kinetics in the positive electrode materials of lithium-ion batteries, resulting in poor electrochemical performance.
By introducing ultrasonic treatment in the preparation process of iron phosphate, amorphous iron phosphate is first prepared, then crystallized and sonicated, and finally obtaining highly dispersed anhydrous iron phosphate through calcination.
The high dispersion and small particle size of iron phosphate particles are achieved, the electrochemical activity of the positive electrode material is improved, and the capacity and rate performance of lithium-ion batteries are enhanced.
Smart Images

Figure CN119706764A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion battery positive electrode materials, and in particular relates to a highly dispersed iron phosphate material and a preparation method and application thereof. Background Art
[0002] In recent years, lithium iron phosphate has attracted more and more attention as a cathode material for lithium-ion batteries due to its high safety, thermal stability and good cycle stability. However, lithium iron phosphate with an olivine structure has problems such as poor conductivity and slow lithium ion diffusion kinetics, which restrict its development and application. As a precursor material of lithium iron phosphate, the morphology, particle size, dispersibility and other properties of iron phosphate will have a direct impact on the properties of lithium iron phosphate.
[0003] At present, the mainstream production method of iron phosphate is precipitation, that is, by mixing the iron source and the phosphorus source, precipitating at a suitable pH, and then further crystallizing and calcining to obtain the iron phosphate product. This method is simple and efficient, but the prepared iron phosphate has problems such as irregular morphology, large particle size, and poor dispersibility, resulting in low capacity and poor electrochemical performance of the prepared iron lithium.
[0004] Prior art such as CN105118995A discloses a method of introducing ultrasound during the synthesis / oxidation process to reduce the primary particle size of iron phosphate and reduce the width of particle size distribution, thereby achieving the effect of improving the electrochemical performance of lithium iron, but the improvement effect is limited. Summary of the invention
[0005] In response to the above technical problems, the present application provides a highly dispersed iron phosphate material and a preparation method thereof, a positive electrode material, and a lithium-ion battery.
[0006] To achieve the above objectives, this application proposes the following technical solutions: In a first aspect, a highly dispersed iron phosphate is provided, wherein the primary particle size of the iron phosphate is 50-100 nm; the particle size D50 of the secondary particles of the iron phosphate is 3.0-4.0 μm, the particle size D90 of the secondary particles is 7.0-8.5 μm, the particle size D10 of the secondary particles is 1.0-1.2 μm, and the value of the diameter distance (D90-D10) / D50 of the secondary particles is 1.8-2.0; the specific surface area of the iron phosphate is 10-12 m 2 / g.
[0007] In a second aspect, a method for preparing highly dispersed ferric phosphate is provided, comprising: S1, preparing solution A with an iron source as a raw material, and preparing mixed solution B with a phosphorus source, an oxidant and aqueous ammonia as raw materials; using solution A as a base liquid, introducing mixed solution B into the base liquid, performing a precipitation reaction to obtain a first slurry, and performing solid-liquid separation to obtain a first solid; S2, adding water to the first solid to prepare a second slurry; adding phosphoric acid to the second slurry, heating to 80-100° C. and performing a first insulation until the second slurry changes from light yellow to white, and continuing a second insulation to obtain a third slurry; performing ultrasonic treatment during the first insulation process; S3, washing and solid-liquid separation of the third slurry to obtain a second solid, and drying the second solid to obtain ferric phosphate dihydrate powder; S4. calcining the dihydrate iron phosphate powder to obtain anhydrous highly dispersed iron phosphate.
[0008] Furthermore, in step S2, the frequency of the ultrasonic treatment during the first insulation process is 10-40 kHz.
[0009] Furthermore, in step S2, the second insulation time is 1 to 2 hours.
[0010] Furthermore, in step S2, the amount of phosphoric acid added is determined to maintain the pH of the slurry at 1.6-2.0; and the phosphoric acid is concentrated phosphoric acid.
[0011] Furthermore, in step S2, the second insulation process is subjected to ultrasonic treatment; the frequency of the ultrasonic treatment is 10-40 kHz.
[0012] Furthermore, in step S2, the solid content of the second slurry is 5-15%, preferably 7.5-15%.
[0013] Furthermore, in step S2, the preparation of the second slurry includes: slurrying the first solid with water; the slurrying is performed under stirring.
[0014] Furthermore, in step S1, the temperature of the precipitation reaction is 40-55°C.
[0015] Furthermore, in step S1, the mixed solution B is added for 60 to 150 minutes.
[0016] Furthermore, in step S1, the precipitation reaction is carried out under stirring conditions.
[0017] Furthermore, in step S1, during the precipitation reaction, after the mixed solution B is introduced, the pH value of the reaction system is adjusted to 1.8-2.0, and the reaction is continued.
[0018] Furthermore, in step S1, the mass concentration of iron in the solution A is 5-10%.
[0019] Furthermore, in step S1, the mass concentration of phosphorus in the mixed solution B is 3-10%.
[0020] Furthermore, in step S1, the molar ratio of iron in the iron source solution to ammonia water in the mixed solution is 1:1-1.1.
[0021] Furthermore, in step S1, the oxidant is hydrogen peroxide.
[0022] Furthermore, in step S4, the calcination temperature is 530-600° C.; and the calcination time is 2-4 hours.
[0023] In a third aspect, a positive electrode material is provided, which is prepared using the aforementioned iron phosphate or the iron phosphate prepared by the aforementioned method as a raw material; the positive electrode material is lithium iron phosphate or lithium manganese iron phosphate.
[0024] In a fourth aspect, a lithium-ion battery is provided, comprising the aforementioned positive electrode material.
[0025] Compared with the prior art, one or more of the above technical solutions can achieve at least one of the following beneficial effects: The present application provides highly dispersed iron phosphate, wherein the primary particle size of the iron phosphate is 50-100 nm, the particle size D50 of the secondary particles of the iron phosphate is 3.0-4.0 μm, the particle size D90 of the secondary particles is 7.0-8.5 μm, the particle size D10 of the secondary particles is 1.0-1.2 μm, and the value of the diameter distance (D90-D10) / D50 of the secondary particles is 1.8-2.0, and the specific surface area of the iron phosphate is 10-12 m 2 / g; the primary particles of the iron phosphate have a small particle size and good dispersibility, and the secondary particles have a small particle size, a narrow particle size distribution, and a high specific surface area. When the iron phosphate is used to prepare positive electrode materials such as lithium iron phosphate or lithium manganese iron phosphate, the secondary particles have a small particle size and a narrow particle size distribution, which is conducive to improving the grinding efficiency and will not be difficult to crush, which is conducive to the mass production of iron lithium and reduces production costs; and because the primary particles of the iron phosphate have a small particle size, it is conducive to the subsequent preparation of positive electrode materials with smaller primary particle sizes, which are more fully in contact with the electrolyte, which is conducive to the insertion / extraction of lithium ions and the improvement of the electrochemical activity of the positive electrode material, thereby achieving the effect of improving the battery capacity and rate performance.
[0026] The preparation method provided in the present application first prepares amorphous iron phosphate, then crystallizes the amorphous iron phosphate, performs ultrasonic treatment during the crystallization process, and subsequently calcines the crystallized iron phosphate dihydrate to prepare iron phosphate with small primary particle size, good dispersibility, small agglomeration and high specific surface area. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0028] Figure 1 These are SEM images of ferric phosphate dihydrate prepared in Example 1 and Comparative Example 1, wherein (a) corresponds to Comparative Example 1, and (b) corresponds to Example 1.
[0029] Figure 2 The anhydrous ferric phosphate prepared by Example 1 and Comparative Example 1, wherein (a) corresponds to Comparative Example 1, and (b) corresponds to Example 1.
[0030] Figure 3 This is the XRD pattern of the anhydrous iron phosphate prepared in Example 1.
[0031] Figure 4 The charge and discharge curves of the battery assembled with the positive electrode materials prepared in Example 1 and Comparative Example 1 at 0.1C.
[0032] Figure 5 The charge and discharge curves of the battery assembled with the positive electrode materials prepared in Example 1 and Comparative Example 1 at 1C. DETAILED DESCRIPTION
[0033] The iron phosphate particles prepared by the precipitation method are large in size and poor in dispersibility. In view of this phenomenon, ultrasonic treatment is performed during the process of preparing iron phosphate by co-precipitation, which is beneficial to reducing the size and agglomeration of iron phosphate particles and improving dispersibility. However, the modification effect is limited. Based on this, the applicant has found through research that by first preparing amorphous iron phosphate, then crystallizing the amorphous iron phosphate, and performing ultrasonic treatment during the crystallization process, and then calcining the crystallized iron phosphate dihydrate, it is possible to prepare iron phosphate with small primary particle size, good dispersibility, small agglomeration (small secondary particle size, narrow distribution, good dispersibility) and high specific surface area. The applicant has found through research that This may be because during the crystallization process, amorphous ferric phosphate will dissolve and recrystallize. In the early stage of the reaction, the nucleation speed of tiny crystal nuclei is fast and the number of crystal nuclei is large, which makes the viscosity of the reaction system rise rapidly and the probability of collision between particles increases, which is not conducive to the formation and dispersion of product particles. During the crystallization process, ultrasonic treatment can continuously break up larger particles, reduce the surface tension of the liquid, prevent the agglomeration of tiny crystal nuclei, make them evenly dispersed in the solution, or adsorb on the undissolved amorphous ferric phosphate, so that the grains of dihydrate ferric phosphate grow stably and evenly, so as to significantly reduce the size of iron phosphate particles, improve the dispersibility of particles, and increase the specific surface area.
[0034] The present invention provides nanometer highly dispersed ferric phosphate, wherein the primary particle size of the ferric phosphate is 50-100 nm; the particle size D50 of the secondary particle of the ferric phosphate is 3.0-4.0 μm, the particle size D90 of the secondary particle is 7.0-8.5 μm, the particle size D10 of the secondary particle is 1.0-1.2 μm, and the value of (D90-D10) / D50 is 1.8-2.0; the specific surface area of the ferric phosphate is 10-12 m 2 / g.
[0035] In the present invention, when the particle size distribution width of iron phosphate increases, the number of large particles also increases. When preparing iron lithium, the material is not easy to grind, which affects the grinding efficiency. In addition, the grinding limit is hundreds of nanometers, and particles below the grinding limit size are difficult to continue to break. Therefore, the more primary particles with initial small size, the smaller the primary particles of the prepared positive electrode material are, and the smaller particles are in more complete contact with the electrolyte, which is conducive to the insertion / extraction of lithium ions and the improvement of the electrochemical activity of the positive electrode material, thereby achieving the effect of improving the battery capacity and rate performance.
[0036] The present invention provides a method for preparing nano highly dispersed ferric phosphate, comprising: S1, preparing solution A with an iron source as a raw material, and preparing mixed solution B with a phosphorus source, an oxidant and aqueous ammonia as raw materials; using solution A as a base liquid, introducing mixed solution B into the base liquid, performing a precipitation reaction to obtain a first slurry, and performing solid-liquid separation to obtain a first solid; S2, adding water to the first solid to prepare a second slurry; adding phosphoric acid to the second slurry, heating to 80-100° C. and performing a first insulation until the second slurry changes from light yellow to white, and continuing a second insulation to obtain a third slurry; performing ultrasonic treatment during the first insulation process; S3, washing and solid-liquid separation of the third slurry to obtain a second solid, and drying the second solid to obtain ferric phosphate dihydrate powder; S4. calcining the dihydrate iron phosphate powder to obtain anhydrous highly dispersed iron phosphate.
[0037] In some preferred embodiments, in step S2, the frequency of the ultrasonic treatment during the first insulation process is 10-40 kHz, for example, 10 kHz, 15 kHz, 20 kHz, 25 kHz, 30 kHz, 35 kHz, 40 kHz, etc.
[0038] In some preferred embodiments, in step S2, the second insulation time is 1 to 2 hours, for example, 1 hour, 1.2 hours, 1.5 hours, 1.8 hours, 2 hours, etc.; In some preferred embodiments, in step S2, the amount of phosphoric acid added is determined to maintain the pH of the slurry at 1.6-2.0, for example, 1.6, 1.7, 1.8, 1.9, 2.0, etc.; the phosphoric acid is preferably concentrated phosphoric acid, and the concentrated phosphoric acid can be used in a conventional concentration in the art, for example, 70-90%.
[0039] In some preferred embodiments, in step S2, ultrasonic treatment is performed during the second insulation process, which is conducive to more thorough crystallization; preferably, the frequency of the ultrasonic treatment during the second insulation process is 10~40kHz, for example, 10kHz, 15kHz, 20kHz, 25kHz, 30kHz, 35kHz, 40kHz, etc.
[0040] In some preferred embodiments, in step S2, the solid content of the second slurry is 5-15%. A reduction in solid content will reduce the viscosity of the crystallization system and the probability of collision between crystals, thereby reducing the particle size of the white material after crystallization, reducing the particle size of the iron phosphate prepared by sintering, and increasing its specific surface area. However, the solid content will reduce production efficiency, and when the addition of phosphoric acid remains unchanged, it often leads to an extension of the crystallization time, further reducing production efficiency. Therefore, a further preferred solid content is 7.5-15%, and more preferably 10-15%.
[0041] The preparation of the second slurry includes: beating the first solid with water; the beating is performed under stirring; the stirring speed can be conventionally controlled as long as it can ensure that the solid is well dispersed in the water, for example, it can be 300-500rpm. It is further preferred that the beating is performed under stirring and ultrasonic treatment; the frequency of the ultrasonic treatment is 10-40kHz, and the ultrasonic treatment can further improve the dispersion of particles in the slurry. However, it is worth noting that the ultrasonic treatment during the beating process is not a necessary operation, but an optional operation.
[0042] In some preferred embodiments, in step S1, the temperature of the precipitation reaction is 40-55°C, for example, 40°C, 42°C, 45°C, 48°C, 50°C, 52°C, 55°C, etc.
[0043] In some preferred embodiments, in step S1, the adding time of the mixed solution is 60 to 150 min, for example, 60 min, 70 min, 80 min, 90 min, 100 min, 110 min, 120 min, 130 min, 140 min, 150 min, etc.
[0044] In some preferred embodiments, in step S1, the precipitation reaction is carried out under stirring conditions; the stirring speed can be a conventional speed for preparing ferric phosphate by precipitation method in the art, for example, it can be 300-500 rpm.
[0045] In some preferred embodiments, in step S1, during the precipitation reaction, after the mixed solution is introduced, the pH value of the reaction system is adjusted to 1.8-2.0 (e.g., 1.8, 1.9, 2.0, etc.), and the reaction is continued. The pH adjustment can be achieved by conventional control, for example, ammonia water can be used as a pH adjuster for adjustment and control.
[0046] In step S1, the iron source can be a conventional iron source prepared from ferric phosphate, specifically, it can be at least one of ferrous sulfate, an industrial grade ferrous sulfate, ferrous nitrate, ferrous chloride, ferrous oxalate, ferrous acetate, ferrous carbonate, and ferric carbonate, which is a byproduct of titanium dioxide. It is worth noting that when the iron source is used as a raw material to prepare solution A, when the iron source is an insoluble iron source, the iron source can be prepared into solution A by adding an acidic solution. Of course, even if the raw material is a soluble iron source, an acidic solution can be added as appropriate. Such process steps and raw materials can be conventional processes and raw materials for preparing ferric phosphate in the art.
[0047] In some preferred embodiments, in step S1, the phosphorus source is at least one of diammonium dihydrogen phosphate, phosphoric acid, diammonium hydrogen phosphate, ammonium phosphate, disodium hydrogen phosphate, sodium dihydrogen phosphate, sodium phosphate, potassium dihydrogen phosphate, dipotassium hydrogen phosphate, and potassium phosphate.
[0048] In step S1, the oxidant can be a liquid oxidant (hydrogen peroxide), a solid oxidant (sodium persulfate, sodium chlorate, sodium thiosulfate, etc.) and a gaseous oxidant (ozone). However, solid oxidants are usually prone to introduce impurities that affect product purity, and the safety of ozone is relatively poor. In some preferred embodiments, in step S1, the oxidant is hydrogen peroxide.
[0049] In step S1, the iron source and the oxidant can be taken according to the conventional ratio for preparing ferric phosphate in the art, for example, the molar ratio of iron in the iron source to the oxidant is 1:0.7~1, such as 1:0.7, 1:0.8, 1:0.9, 1:1, etc.
[0050] In some preferred embodiments, in step S1, the mass concentration of iron in the iron source solution is 5-10%, for example, 5%, 6%, 7%, 8%, 9%, 10%, etc. When the concentration is too high, the viscosity of the synthetic solution system will be too large, which is not conducive to the synthesis and dispersion of the yellow material, and it is easy to cause crystal precipitation in the solution at low temperatures. When the concentration is too low, too much ammonia water is required to adjust the pH value of the system after the subsequent feeding is completed. The presence of too much ammonium ions will affect parameters such as product particle size and specific surface area, and too low a concentration will also reduce production efficiency.
[0051] In some preferred embodiments, in step S1, the mass concentration of phosphorus in the mixed solution is 3-10%, for example, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, etc.
[0052] In some preferred embodiments, in step S1, the molar ratio of iron in the iron source solution to aqueous ammonia is 1:1-1.1, for example, 1:1, 1:1.01, 1:1.02, 1:1.03, 1.04, 1:1.05, 1:1.06, 1:1.07, 1:1.08, 1:1.09, 1:1.10, etc.
[0053] In step S1, the phosphorus source and the iron source can be taken in a conventional ratio for preparing ferric phosphate in the art. For example, the molar ratio of the iron source to the phosphorus source in the phosphorus source is 1:1~1.2, for example, 1:1, 1:1.02, 1:1.05, 1:1.08, 1:1.1, 1:1.12, 1:1.15, 1:1.18, 1:1.2, etc.
[0054] In some preferred embodiments, in step S4, the calcination temperature is 530-600°C, for example, 530°C, 540°C, 550°C, 560°C, 570°C, 580°C, 590°C, 600°C, etc. Too high a sintering temperature will cause the iron phosphate particles to stick together, resulting in an increase in particle size and a decrease in specific surface area; too low a sintering temperature will lead to incomplete crystal conversion. It is preferred to calcine at 530-600°C to prevent particle adhesion while ensuring complete crystal conversion; the calcination time is 2-4h, for example, 2h, 2.5h, 3h, 3.5h, 4h, etc.
[0055] The present invention provides a positive electrode material, which is prepared by using the above-mentioned iron phosphate or the iron phosphate prepared by the above-mentioned method as a raw material; the positive electrode material is lithium iron phosphate or lithium manganese iron phosphate.
[0056] The present invention provides a lithium ion battery, comprising the above-mentioned positive electrode material.
[0057] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the specification, but the protection scope of the present invention is not limited to the following specific embodiments.
[0058] Example 1 (1) Weigh the titanium dioxide ferrous sulfate and ammonium dihydrogen phosphate after impurity removal in a molar ratio of Fe to P of 1:1, prepare ferrous sulfate solution and ammonium dihydrogen phosphate solution with a mass concentration of 7% respectively, and set aside; take an excess of hydrogen peroxide solution (Fe in the Fe source and H in the hydrogen peroxide) 2 O 2 The molar ratio of the Fe source to the ammonia water is 1:0.8), and set aside; take a certain amount of ammonia solution (the molar ratio of the Fe source to the ammonia water calculated as ammonium ions is 1:1.05), and set aside.
[0059] (2) The diammonium dihydrogen phosphate solution, the ammonia water and the hydrogen peroxide solution are uniformly mixed to obtain a first mixed system, wherein the mass concentration of phosphorus in the first mixed system is 3%.
[0060] (3) placing the ferrous sulfate solution in a reaction kettle and heating it to 45°C, controlling the stirring speed to 500 rpm, then pumping the solution of the first mixed system into the reaction kettle through a peristaltic pump, controlling the feeding time to 60 min, and reacting. After the feeding is completed, controlling the pH of the reaction system to 1.9 with ammonia water, controlling the stirring speed to 500 rpm, and keeping the temperature for 30 min, washing and filtering the precipitate to obtain a first filter cake.
[0061] (4) Place the first filter cake into the reactor, add water to slurry, control the solid content to 10%, and the slurry speed to 500 rpm. Place an industrial-grade ultrasonic vibrator into the reactor, and control the ultrasonic frequency to 40 kHz; (5) Add an appropriate amount of concentrated phosphoric acid into the reactor, control the solution pH to 1.8, and heat to 95°C. After keeping warm for 1 hour, the slurry turns white. After the slurry turns white, continue to keep warm for 2 hours. Wash and filter the precipitate to obtain a second filter cake. The heating and two stages of heat preservation are carried out under ultrasonic and mechanical stirring conditions. The ultrasonic frequency is 40 kHz and the stirring speed is 500 rpm.
[0062] (6) After drying the second filter cake, white iron phosphate dihydrate powder is obtained, and the SEM image is as follows: Figure 1 (b) shown.
[0063] (7) Calcine the iron phosphate dihydrate powder at 550°C for 120 min to obtain a light yellow FePO 4 The SEM image of the obtained product is as follows Figure 2 As shown in (b), it can be seen from the figure that the primary particle size of anhydrous iron phosphate is 50~100nm. The XRD pattern of the obtained product is shown in Figure 3 As shown, from Figure 3 It can be seen that pure phase anhydrous iron phosphate was synthesized.
[0064] Example 2 The difference between this embodiment and embodiment 1 is that in step (5), the heating and the first stage of heat preservation are both carried out under ultrasonic and mechanical stirring conditions, the ultrasonic frequency is 40 kHz, and the stirring speed is 500 rpm; and the second stage of heat preservation is only mechanically stirred, and the stirring speed is 500 rpm.
[0065] Example 3 The only difference between this embodiment and embodiment 1 is that in step (5), the ultrasonic frequencies of the heating and the two-stage insulation are both 30 kHz.
[0066] Example 4 The only difference between this embodiment and embodiment 1 is that in step (5), the ultrasonic frequencies of the heating and the two-stage insulation are both 20 kHz.
[0067] Example 5 The only difference between this embodiment and embodiment 1 is that in step (5), the ultrasonic frequencies of the heating and the two-stage insulation are both 10 kHz.
[0068] Example 6 The only difference between this embodiment and embodiment 1 is that in step (3), ultrasonic treatment is also performed during the entire reaction process, and the ultrasonic frequency is controlled to be 40 kHz.
[0069] Comparative Example 1 The difference between this comparative example and Example 1 is that in step (5), the heating and the two-stage heat preservation are only carried out under mechanical stirring conditions, and no ultrasonic treatment is performed.
[0070] The SEM image of the obtained iron phosphate dihydrate powder is as follows: Figure 1 (a) As shown; the obtained light yellow anhydrous FePO 4 The SEM images are as follows Figure 2 As shown in (a), it can be seen from the figure that the primary particle size of anhydrous ferric phosphate is 70~320nm.
[0071] By comparing the dihydrate iron phosphate powder and anhydrous iron phosphate obtained in Example 1 with those in Comparative Example 1, it can be found that the primary particle size and secondary particle size of the dihydrate iron phosphate prepared in Example 1 are smaller, and the particle size distribution of the primary particles and the secondary particles is also narrower; the particle size of the primary particles and the secondary particles of the anhydrous iron phosphate obtained after calcination is also smaller, and the dispersibility of the primary particles and the secondary particles is significantly better than that of the anhydrous iron phosphate obtained in Comparative Example 1.
[0072] Comparative Example 2 The difference between this comparative example and Example 1 is that in step (5), the heating and the first stage of heat preservation are carried out only under mechanical stirring conditions without ultrasonic treatment, and the second stage of heat preservation is carried out under mechanical stirring and ultrasonic treatment; the stirring speed is 500 r / min and the ultrasonic power is 40 kHz.
[0073] Comparative Example 3 (1) Weigh the titanium dioxide ferrous sulfate and ammonium dihydrogen phosphate after impurity removal in a molar ratio of Fe to P of 1:1, prepare ferrous sulfate solution and ammonium dihydrogen phosphate solution with a mass concentration of 7% respectively, and set aside; take an excess of hydrogen peroxide solution (Fe source and H 2 O 2 The molar ratio of the Fe source to the ammonia water is 1:0.8), and set aside; take a certain amount of ammonia solution (the molar ratio of the Fe source to the ammonia water calculated as ammonium ions is 1:1.05), and set aside.
[0074] (2) The ammonium dihydrogen phosphate solution is uniformly mixed with the ammonia water and the hydrogen peroxide solution to obtain a first mixed system. In the first mixed system, the mass concentration of the ammonium dihydrogen phosphate is 3%.
[0075] (3) Placing the titanium dioxide ferrous sulfate solution in a reactor and heating it to 45°C, controlling the stirring speed to 500 rpm, then pumping the solution of the first mixed system into the reactor through a peristaltic pump, controlling the feeding time to 60 min, and reacting. After the feeding is completed, controlling the pH of the reaction system to 1.9 with ammonia water, controlling the stirring speed to 500 rpm, and keeping the temperature for 30 min, washing and filtering the precipitate to obtain the first filter cake; performing ultrasonic treatment during the entire reaction process, and controlling the ultrasonic frequency to 40 kHz.
[0076] (4) Place the first filter cake into the reactor, add water to pulp, control the solid content to 15%, and the pulping speed to 500 rpm. Place an industrial-grade ultrasonic vibrator into the reactor and control the ultrasonic frequency to 40 kHz; (5) Add an appropriate amount of concentrated phosphoric acid into the reactor, control the solution pH to 1.8, and heat to 95°C. After keeping warm for 1 hour, the slurry turns white. After the slurry turns white, continue to keep warm for 2 hours. Wash and filter the precipitate to obtain a second filter cake. The heating and two stages of heat preservation are carried out under mechanical stirring conditions, and the stirring speed is 500 rpm.
[0077] (6) After the second filter cake is dried, white iron phosphate dihydrate powder is obtained.
[0078] (7) Calcine the iron phosphate dihydrate powder at 550°C for 120 min to obtain a light yellow FePO 4 .
[0079] Example 7 The difference between this embodiment and embodiment 1 is that the solid content is controlled differently when adding water for pulping in step (4). In this embodiment, the solid content is 12.5%.
[0080] Example 8 The difference between this embodiment and embodiment 1 is that the solid content is controlled differently when adding water for pulping in step (4). In this embodiment, the solid content is 15%.
[0081] Example 9 The difference between this embodiment and embodiment 1 is that the solid content is controlled differently when adding water for pulping in step (4). In this embodiment, the solid content is 7.5%; and in step (5), the slurry turns white after being heated to 95° C. and kept warm for 3 hours.
[0082] Comparative Example 4 The difference between this comparative example and Example 1 is that the solid content is controlled differently when adding water for pulping in step (4). In this example, the solid content is 17.5%.
[0083] Example 10 The only difference between this embodiment and embodiment 1 is that in step (5), the stirring speed is 400 rpm.
[0084] Embodiment 11 The only difference between this embodiment and embodiment 1 is that in step (5), the stirring speed is 300 rpm.
[0085] Comparative Example 5 The only difference between this comparative example and Example 1 is that in step (5), the stirring speed is 200 rpm.
[0086] Comparative Example 6 The only difference between this comparative example and Example 1 is that in step (5), the stirring speed is 100 rpm.
[0087] Comparative Example 7 The only difference between this comparative example and Example 1 is that in step (5), no stirring is performed.
[0088] The anhydrous FePO prepared in each example and comparative example was prepared by the following method. 4 The physical and chemical characteristics of the test: Specific surface area: GB / T 13390-2008 Determination of specific surface area of metal powder-Nitrogen adsorption method was used, and the specific surface area was tested using a specific surface meter.
[0089] Particle size distribution: Reference HG / T 4701 Iron phosphate for batteries 5.11 particle size determination method; mix the sample, weigh 0.1gg sample, place it in a 100mL clean beaker filled with 50mL water, and after ultrasonication for 15 minutes, use Bettersize2600 laser particle size distribution analyzer wet method system for detection.
[0090] Anhydrous FePO prepared in each embodiment and comparative example 4 The characterization parameters are shown in Table 1. By comparing the parameters in Table 1, it can be seen that the anhydrous ferric phosphate prepared in each embodiment has a higher surface area and a narrower secondary particle size distribution (that is, the consistency of the secondary particles is good, which also reflects the good dispersibility of the secondary particles). The primary particle size of the prepared anhydrous ferric phosphate is 50-100nm, the particle size D50 of the secondary particles is 3.0-4.0μm, the particle size D90 of the secondary particles is 7.0-8.5μm, and the particle size D10 of the secondary particles is 1.0-1.2μm; the value of (D90-D10) / D50 is 1.8-2.0, and the specific surface area of ferric phosphate is 10-12m2 / g.
[0091] By comparing the product characterization parameters of Example 1, Example 2, Comparative Example 1 and Comparative Example 2, it can be seen that the ultrasonic treatment in the first insulation process in step (5) can significantly improve the anhydrous FePO 4 The specific surface area of the anhydrous FePO4 is larger, and the particle size distribution is narrower. Although the ultrasonic treatment in the second heat preservation process in step (5) can improve the 4 The specific surface area is increased and the particle size distribution is narrower, but the improvement effect is not obvious and the expected purpose cannot be achieved.
[0092] By comparing the product characterization parameters of Comparative Example 1 and Comparative Example 3, it can be seen that although the ultrasonic treatment in the preparation process of amorphous iron phosphate in step (3) can improve the characterization parameters of anhydrous iron phosphate, the improvement effect is not good. By comparing the product characterization parameters of Example 1 and Example 6, it can be seen that after the introduction of ultrasonic treatment in the insulation process of step (5) significantly optimizes the characterization parameters of the product, the ultrasonic treatment in the preparation process of amorphous iron phosphate in step (3) will not have a significant effect on the characterization parameters of anhydrous iron phosphate.
[0093] Table 1 Application Examples Preparation of lithium iron phosphate, including: (1) Weigh appropriate amounts of iron phosphate, lithium carbonate, glucose and PEG-2000 powder and add them into a ball mill. The molar ratio of iron phosphate to lithium carbonate is 1:1.03, and the masses of glucose and PEG-2000 are 6% and 4% of the mass of iron phosphate, respectively.
[0094] (2) Add appropriate amount of deionized water and control the solid content to 30% for ball milling. The ball milling parameters are 500 rpm and ball milling for 6 hours.
[0095] (3) The ball-milled slurry was spray-dried, and the spray-dried powder was placed in a tube furnace and sintered at 760° C. for 8 hours under a nitrogen atmosphere to obtain carbon-coated lithium iron phosphate powder.
[0096] Battery Assembly: The lithium iron phosphate powder prepared in Example 1 and Comparative Example 1, PVDF and conductive carbon were respectively added into a homogenizer at a mass ratio of 8:1:1, and an appropriate amount of polyvinyl pyrrolidone was added for homogenization.
[0097] The homogenized slurry was evenly coated onto aluminum foil using a spatula and dried in a vacuum oven overnight.
[0098] The dried material is sliced with a slicer to obtain a positive electrode sheet, and weighed to calculate the loading amount of the active substance. The positive electrode shell, positive electrode sheet, diaphragm, lithium sheet, gasket, spring and negative electrode shell are assembled in sequence, and a proper amount of electrolyte is dripped into them, and placed in a tablet press for tablet packaging to obtain the required buckle electricity for testing.
[0099] The lithium iron phosphate assembled button batteries prepared in Example 1 and Comparative Example 1 were placed in a Xinwei battery testing system for battery performance testing, with a test voltage range of 2.5V to 4.3V and a test temperature of room temperature.
[0100] Figure 4 The charge and discharge curves of the batteries assembled with the positive electrode materials prepared in Example 1 and Comparative Example 1 at 0.1C. It can be seen from the figure that compared with the battery assembled with lithium iron phosphate prepared in Comparative Example 1, the charge and discharge specific capacity of the battery assembled with lithium iron phosphate prepared in Example 1 is significantly improved.
[0101] Figure 5 The charge and discharge curves of the batteries assembled with the positive electrode materials prepared in Example 1 and Comparative Example 1 at 1C. It can be seen from the figure that compared with the battery assembled with lithium iron phosphate prepared in Comparative Example 1, the charge and discharge specific capacity of the battery assembled with lithium iron phosphate prepared in Example 1 is significantly improved, and the improvement is significantly higher than the improvement at a low rate (0.1C), which indicates that the charge and discharge specific capacity and rate performance of the battery assembled with lithium iron phosphate prepared in Example 1 are significantly improved. After analysis, this may be because the primary particle size of the prepared anhydrous iron phosphate is small (50-100nm), the dispersibility is good, and the secondary particle dispersibility is good, so This secondary particle is easily dissociated by grinding, so that the prepared lithium iron phosphate primary particles have a small particle size and good dispersibility. Therefore, they have more complete contact with the electrolyte, which is beneficial to the insertion / extraction of lithium ions and the improvement of the electrochemical activity of the positive electrode material, thereby achieving the effect of improving the battery capacity and rate performance. However, the anhydrous iron phosphate primary particles prepared in Comparative Example 1 have a larger particle size and poor dispersibility, and the secondary particles also have poor dispersibility. The secondary particles are difficult to grind and dissociate. The prepared lithium iron phosphate primary particles have a larger particle size and poor dispersibility, so they have relatively poor contact with the electrolyte, which is not conducive to the insertion / extraction of lithium ions. As a result, the assembled battery has relatively poor capacity and rate performance.
[0102] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. Highly dispersed ferric phosphate, characterized in that: The primary particle size of the iron phosphate is 50-100 nm; the particle size D50 of the secondary particle of the iron phosphate is 3.0-4.0 μm, the particle size D90 of the secondary particle is 7.0-8.5 μm, the particle size D10 of the secondary particle is 1.0-1.2 μm, and the value of (D90-D10) / D50 is 1.8-2.0; the specific surface area of the iron phosphate is 10-12 m 2 / g.
2. A method for preparing highly dispersed ferric phosphate, characterized in that: include: S1, preparing solution A with an iron source as a raw material, and preparing a mixed solution B with a phosphorus source, an oxidant and aqueous ammonia as raw materials; Solution A is used as a base liquid, mixed solution B is introduced into the base liquid, a precipitation reaction is performed to obtain a first slurry, and a first solid is obtained by solid-liquid separation; S2, adding water to the first solid to prepare a second slurry; adding phosphoric acid to the second slurry, heating to 80-100° C. and performing a first insulation until the second slurry changes from light yellow to white, and continuing a second insulation to obtain a third slurry; performing ultrasonic treatment during the first insulation process; S3, washing and solid-liquid separation of the third slurry to obtain a second solid, and drying the second solid to obtain ferric phosphate dihydrate powder; S4. calcining the dihydrate iron phosphate powder to obtain anhydrous highly dispersed iron phosphate.
3. The method for preparing highly dispersed ferric phosphate according to claim 2, characterized in that: In step S2, the frequency of the ultrasonic treatment during the first insulation process is 10-40 kHz.
4. The method for preparing highly dispersed ferric phosphate according to claim 2, characterized in that: In step S2, the second insulation time is 1 to 2 hours; In step S2, the amount of phosphoric acid added is determined to maintain the pH of the slurry at 1.6-2.0; the phosphoric acid is concentrated phosphoric acid; In step S2, the second heat preservation process is subjected to ultrasonic treatment; The frequency of the ultrasonic treatment is 10-40 kHz.
5. The method for preparing highly dispersed ferric phosphate according to claim 2, characterized in that: In step S2, the solid content of the second slurry is 5-15%, preferably 7.5-15%; In step S2, the preparation of the second slurry includes: slurrying the first solid with water; the slurrying is performed under stirring.
6. The method for preparing highly dispersed ferric phosphate according to claim 2, characterized in that: In step S1, the temperature of the precipitation reaction is 40-55°C; In step S1, the mixed solution B is added for 60 to 150 minutes; In step S1, the precipitation reaction is carried out under stirring conditions; In step S1, during the precipitation reaction, after the mixed solution B is introduced, the pH value of the reaction system is adjusted to 1.8-2.0, and the reaction is continued.
7. The method for preparing highly dispersed ferric phosphate according to any one of claims 2 to 6, characterized in that: In step S1, the mass concentration of iron in the solution A is 5-10%; In step S1, the mass concentration of phosphorus in the mixed solution B is 3-10%; In step S1, the molar ratio of iron in the iron source solution to ammonia water in the mixed solution is 1:1-1.1; In step S1, the oxidant is hydrogen peroxide.
8. The method for preparing highly dispersed ferric phosphate according to claim 2, characterized in that: In step S4, the calcination temperature is 530-600° C.; and the calcination time is 2-4 hours.
9. A positive electrode material, characterized in that The method is prepared by using the iron phosphate as claimed in claim 1 or the iron phosphate prepared by the method as claimed in any one of claims 2 to 8 as a raw material; the positive electrode material is lithium iron phosphate or lithium manganese iron phosphate.
10. A lithium ion battery, characterized in that Comprising the positive electrode material as claimed in claim 9.
Citation Information
Patent Citations
Production method of battery-grade iron phosphate
CN105118995A
Ultrafine porous structure battery-grade iron phosphat and preparation method thereof
CN112723332A
Iron phosphate material as well as preparation method and application thereof
CN118545688A
Method for preparing iron phosphate substance by adding reductive organic matter
WO2018064862A1
Cited By
Positive electrode material as well as preparation method and application thereof
CN120955127A